Kinetic study for biofilm manganese removal - Nadzirah, Md Lazim (2010)
Objective of this study is to determine the kinetic parameters of manganese (Mn) removal for the biofilm from two different sources; which were from drain and soil. There are four kinetic parameters needed to be determined which were yield coefficient (Y), decay rate constant (kd), microbial growth rate (µ), and substrate concentration (Ks); the calculation was based on Monod kinetic model. The process for determining kinetic parameters of each biofilm included the acclimatization of biofilm, total suspended solids tests (TSS), Mn tests and chemical oxygen demand (COD) tests. Sequencing batch biofilm reactor (SBR) is used in this study and two parameters are tested in the experiment; Mn and COD concentration. Results showed that the kinetic value for drain biofilm of Mn concentration parameter were Y = 2.9912 mg TSS/mg Mn, kd -1= 1.214 day, µmax -1= 1.374 daymax , and Ks = 0.4262 mg/L Mn. The soil biofilm for Mn concentration parameter showed the value of kinetic as Y = 0.1317 mg TSS/mg Mn, k d -1= 1.836 day, µmax -1= 1.846 day, and Ks = 0.0433 mg/L Mn. For the research on the COD concentration parameter, the values of kinetic for drain biofilm are Y = 0.0078 mg TSS/mg COD, kd -1= 1.0519 day, µ =1.136 daymax-1, and Ks = 4.403 mg/L COD. Soil biofilm showed the kinetic values of Y = 0.0117 mg TSS/mg COD, k= 1.8348 day-1, µmax -1 = 1.844 dayd , and Ks = 0.0433 mg/L COD. By the evaluation of COD and Mn removal from wastewater, from the way of kinetic parameter estimation provide knowledge for future planning, designing and modelling of wastewater treatment plant.